1995
DOI: 10.1111/j.1949-8594.1995.tb15775.x
|View full text |Cite
|
Sign up to set email alerts
|

High School Students' Views about the Nature of Science: Results from Three Countries

Abstract: During the last two decades, massive efforts have been directed at uncovering different science concepts held by school age students. This particular study focused on identifying high school students' views regarding the nature of science. Thirty‐two students were chosen from each of the following three countries: Canada, the United States, and Australia. Interviews were conducted with each student. The interview protocol contained the same core questions with an opportunity built in to allow both the student … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 9 publications
1
24
0
Order By: Relevance
“…' Leach, Driver, Millar, and Scott (1997) began exploring these developmental issues and found that students 9-16 of age do have different patterns of understanding of the nature of scientific knowledge. Previous studies (e.g., Griffiths & Barman, 1995;Meichtry, 1992) found that elementary students do not improve their views of NOS simply by proceeding through inquiry-oriented science activities. However, similar to what was found by Akerson and Volrich (2006) and Khishfe and Abd-El-Khalick (2002), it is apparent that the explicit emphasis on NOS elements worked very well for the first grade and fifth and sixth grade students, whose responses became more elaborate and in-line with reform recommendations at the conclusion of the school year.…”
Section: Elementary Students' Views Of Nosmentioning
confidence: 88%
“…' Leach, Driver, Millar, and Scott (1997) began exploring these developmental issues and found that students 9-16 of age do have different patterns of understanding of the nature of scientific knowledge. Previous studies (e.g., Griffiths & Barman, 1995;Meichtry, 1992) found that elementary students do not improve their views of NOS simply by proceeding through inquiry-oriented science activities. However, similar to what was found by Akerson and Volrich (2006) and Khishfe and Abd-El-Khalick (2002), it is apparent that the explicit emphasis on NOS elements worked very well for the first grade and fifth and sixth grade students, whose responses became more elaborate and in-line with reform recommendations at the conclusion of the school year.…”
Section: Elementary Students' Views Of Nosmentioning
confidence: 88%
“…Nevertheless, empirical data show that a proper understanding of the nature of science is not easy to achieve, even when learners have received specially designed instruction (Lederman, 1992;Meichtry, 1993;Griffiths & Barman, 1995). Recent studies concerning learning in the socio-scientific context have suggested that controversial issues that reveal the social aspects of science could facilitate understanding of the nature of science (Zeidler et al , 2002;Walker & Zeidler, 2003;Sadler & Zeidler, 2004;Yang, forthcoming).…”
Section: Introductionmentioning
confidence: 94%
“…From an educational perspective, studies on student understanding of the nature of scientific knowledge show that students tend to (1) associate laws with a high level of certainty than theories because they are more directly observable (Dagher et al, 2004;McComas & Olson, 1998); (2) demand direct evidence to be offered as proof of a theory (Dagher et al 2004); (3) believe that theories are proven hypotheses (Sandoval & Morrison, 2003) that can become laws when they become confirmed (Dagher et al, 2004;Griffiths & Barman, 1995;McComas & Olson, 1998;Meyling, 1997;Ryan & Aiknhead, 1992). Gibbs and Lawson (1992) analysis of high school biology textbooks show that they promulgate a number of naïve ideas that have been expressed also by students such as describing theory "as hypotheses that have been supported over a long period of time" (p. 137).…”
Section: Theoretical Frameworkmentioning
confidence: 99%